A one health roadmap towards understanding and mitigating emerging Fungal Antimicrobial Resistance: fAMR - Matthew C. Fisher; Fiona Burnett; Clare Chandler; Neil A. R. Gow; Sarah Gurr; Alwyn Hart; Alison Holmes; Robin C. May; Janet Quinn; Tarek Soliman; Nicholas J. Talbot; Helen M. West; et al. (npj Antimicrobials and Resistance)
Abstract The emergence of fungal antimicrobial resistance—fAMR—is having a growing impact on human and animal health, and food security. This roadmap charts inter-related actions that will enhance our ability to mitigate the risk of fAMR. As humanity’s reliance on antifungal chemicals escalates, our understanding of their one-health consequences needs to scale accordingly if we are to protect our ability to manage the global spectrum of fungal disease sustainably.